Os cromossomos sexuais como fonte geradora de diferenciação genética. O gênero Pyrrhulina (Characiformes, Lebiasinidae) como modelo - Ferreira, Pedro Henrique Narciso (Universidade Federal de São Carlos, 2021)
Allopatric processes are generally considered among the main causes of the striking Neotropical biodiversity. However, the role of chromosomal rearrangements and neo-sex chromosomes in genetic diversity and speciation remains still little investigated. Here, we aimed to infer the relative contribution of allopatry, chromosomal rearrangements, and sex chromosomes to genetic divergence in five Pyrrhulina species using population genomic analyses coupled with cytogenetic data. Our results highlighted that the distribution of the genetic diversity is consistent with their chromosomal and geographical data and was mainly influenced by long-distance allopatry. The results of PCoA indicated a clear clustering of species located in the same geographical region, except for P. semifasciata, that is in sympatry with P. brevis. In fastStructure K=4 result, only P. australis and P. marilynae were grouped, and with K=3 P. obermulleri and P. brevis were further combined. In this case, geographically close species showed genetically similarity, indicating speciation mechanisms that are largely dependent of allopatry. The effect of allopatry also were amplified when coupled with the occurrence of chromosomal rearrangements, as observed for P. marilynae, the species with highly rearranged karyotype (2n=32). Besides, the genetic structure analyzes indicated great differentiation in P. semifasciata, suggesting that the presence of the X1X2Y sex chromosome system, exclusively present in individuals of this species, caused high genetic differentiation and showing that such effect was significant even in sympatry. In summary, the distribution of genetic diversity among the analyzed species is mainly influenced long-distance allopatry, but the occurrence of chromosomal rearrangements, especially the sex-related ones contributed to the fixation of genetic differences which may lead to reproductive isolation and a consequent speciation process within the genus
Sex chromosomes as a source of genetic differentiation. The genus Pyrrhulina (Characiformes, Lebiasinidae) as a model
Keywords: Peixes; Cromossomos Sexuais; Diversidade Genética; SNPs; Especiação; Alopatria; Fish; Sex chromosomes; Genetic diversity; Speciation; Allopatry; CIENCIAS BIOLOGICAS::GENETICA